Facial Injuries in Disaster and Earthquake Treatment - Demiröz, Anıl; Yavuz, Ersin (Cerrahpaşa Medical Journal, 2023)
Facial injuries are commonly observed in multitrauma patients. Due to vast blood supply, primary closure should be performed as quickly as possible to prevent infection and blood loss. Although facial fractures can be mostly electively operated on, emergent interventions may be necessary in cases where airway is compromised or visual loss is suspected. Cite this article as: Yavuz E, Demiröz A. Facial injuries in disaster and earthquake treatment. Cerrahpaşa Med J. 2023;47(S1):69-71